Synthesis of HIV NNRTI Doravirine Analogues via Visible-Light Photoredox Decarboxylative Cross-Coupling - Suen, Linda M.; Wang, Cheng; Hunter, David N.; Mitchell, Helen J.; Converso, Antonella; ElMarrouni, Abdellatif (Synthesis, 2018)
A C(sp2)–C(sp3) decarboxylative cross-coupling reaction utilizing dual nickel and photoredox catalysis for rapid parallel synthesis of diverse C-ring analogues of the HIV NNRTI clinical candidate doravirine is developed and described herein. This protocol features an alkylation with readily available and inexpensive methyl bromoacetate followed by hydrolysis to prepare an advanced doravirine intermediate, which undergoes decarboxylative cross-coupling with a variety of aryl and heteroaryl bromides. The mildness, broad applicability, and sustainability of the current methodology are improvements over previously reported procedures and allow for rapid parallel synthesis of analogues. The optimization and scope of this method are reported.
Keywords: HIV; photoredox catalysis; visible light; decarboxylative coupling; NNRTI